2022
DOI: 10.3390/mi13010087
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of the Dual-Mode Lamb Wave Resonator and Dual-Passband Filter

Abstract: Radio frequency (RF) filters with multiple passbands can meet the needs of miniaturization and integration for 5G communications. This paper reports a dual-mode Lamb wave resonator (DLWR) and a dual-passband filter based on DLWRs. The DLWR consists of a piezoelectric film and two interdigital electrode (IDT) arrays with different thicknesses, which leads to the coexistence of two main modes in the resonator. The resonance frequencies of the two modes can be adjusted separately by changing the thicknesses of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The phase velocity of the lowerorder symmetric Lamb wave mode is up to 10,000 m/s [126]. However, there are some parameters that still need optimization to further reduce the noise in the designed sensors and filters and produce low-lose filters and stable oscillators [133][134][135]. In addition, the fabrication of these types of resonators is considered not compatible with some common multiuser fabrication technology which is considered one of the obstacles for us to use it in our research.…”
Section: Lateral Extensional Mode (Le) Contour-mode or Lamb Wave Modementioning
confidence: 99%
“…The phase velocity of the lowerorder symmetric Lamb wave mode is up to 10,000 m/s [126]. However, there are some parameters that still need optimization to further reduce the noise in the designed sensors and filters and produce low-lose filters and stable oscillators [133][134][135]. In addition, the fabrication of these types of resonators is considered not compatible with some common multiuser fabrication technology which is considered one of the obstacles for us to use it in our research.…”
Section: Lateral Extensional Mode (Le) Contour-mode or Lamb Wave Modementioning
confidence: 99%
“…It was demonstrated that the AlN/Al x Sc 1−x N composite films effectively reduced the surface roughness, abnormal grains in films, and mechanical stress, which indicated an effective improvement in film quality. Luo et al [113] designed and simulated a dual-mode Al 0.8 Sc 0.2 N Lamb wave resonator. Different from the two IDT arrays with equal thicknesses in conventional Lamb wave resonators, two IDT arrays with different thicknesses were applied as the top electrode.…”
Section: S0 Mode Alxsc 1−x N-based Lamb Wave Resonatorsmentioning
confidence: 99%
“…The FBAR is composed of an AlN film with a c -axis-tilted angle, which leads to the coexistence of a longitudinal mode and a shear mode. Luo et al [ 14 ] and Yang et al [ 15 ] both proposed dual-band filters based on the modified lamb wave resonator (LWR), as the former one utilized two interdigital electrode (IDT) arrays with different thicknesses, and the latter one exploited the LN thickness difference. Dual-band surface acoustic wave (SAW) filters have been researched as well.…”
Section: Introductionmentioning
confidence: 99%